Valuation of Activision Blizzard, Inc. - Lacina, Kamil; Ryška, Tomáš, 1976-; Kopkáně, Heřman; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
The main goal of this thesis is to provide a valuation of Activision Blizzard, Inc. for a theoretical marginal investor as of 31st December 2021. Activision Blizzard, Inc. is a member of the Fortune 500 and S&P 500 operating in the interactive entertainment and gaming industry. The thesis is divided into the theoretical and practical part. In the theoretical part, the basis of the valuation methods and strategic analysis methodology are introduced. In the practical part, the strategic analysis and the valuation with more detailed theory to the specific concepts are introduced. Valuation of Activision Blizzard, Inc. is performed on a DCF model and comparable valuation mode. The results are further evaluated with the market price. The DCF model evaluated to reach 79,27$ per share as o 31st December 2020. The comparable valuation based on the EV/EBITDA multiple is resulting in a value between 80,06$ and 94,6$ per share. In comparison to the share market price of 92,85$, the valuations suggest, that Activision Blizzard is overvalued as of 31st December 2020.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses